ENGLISH LANGUAGE TEACHING IN BRAZIL AT PUBLIC SCHOOLS - Barbosa de Paula, Rebeca (Revista Gênero e Interdisciplinaridade, 2023)
The present work aims to investigate in some ways why don´t the Brazilian students at public schools get fluent in the English language, besides studying it for many years, and give some possible solutions for that situation. The goal is promoting some strategies that can be used by the teachers to help the students and propitiate the “communicative approach” as the BNCC terms explain by improving the English Language teaching and learning in Brazil at public schools.